Symptoms and Treatment-Related Knowledge of Cancer Patients Receiving Chemotherapy) - Nawaz Ali, Kiran; Shah, Ibrahim (Journal of World Science, 2023)
This study aims to investigate the existing level of knowledge regarding the symptoms, side effects, and treatment plans of cancer patients undergoing chemotherapy. Addressing gaps in literature and enhancing patient education can significantly improve outcomes and reduce cancer-related mortality and morbidity worldwide. Several search engines, including PubMed, CINHAAL, Science Direct, Research Gate, and Google Scholar, were used to conduct a comprehensive and broad literature evaluation. Each database was searched using keywords for "Knowledge OR Health Literacy OR Health Education OR Patient Knowledge AND Chemotherapy OR Symptoms OR Treatment Plan", resulting in the inclusion of 20 relevant articles for the study. The results highlighted the major challenges faced by patients undergoing chemotherapy and the severity of their symptoms, emphasizing the need for improved management strategies. Moreover, there are notable gaps in patient knowledge about chemotherapy and its side effects, underscoring the importance of targeted education programs and strengthened communication between healthcare providers and patients for better outcomes. Knowledge about the symptoms and treatment of cancer patients undergoing chemotherapy is an essential component for better survival and for reducing suffering. It is important to identify patients' knowledge about chemotherapy so that they can receive health education tailored to the needs, capabilities, and preferences of each individual patient.